Statistical evaluation of the effect of formulation on the properties of crude glycerol polyurethane foams - Gama, Nuno V.
In our pursuit of developing ecofriendly materials, the effect of the main components of the formulation used for the preparation of polyurethane foams (PUFs) derived from unrefined crude glycerol (CG) has been systematically studied. A series of PUFs has been prepared using formulations with judicious variations of the percentage of each component. The physical properties of the resulting PUFs were measured and the data collected were statically treated using a four-way functional ANOVA method. From the ANOVA results, the paramount importance that the blowing agent and the surfactant have on the regulation of density and thermal conductivity of PUFs was recognized. Regarding the mechanical properties, the isocyanate content presented a dominant influence on the increase of Young's modulus, toughness and compressive stress of PUFs. (C) 2016 Elsevier Ltd. All rights reserved.